Ensuring Meticulousness of Homeopathic Pharmacy for Accu racy in Medicinal Plant Identifica tion and Collection through Critical Taxonomical Intervention (Advancements in Homeopathic Research, 2024)
Homeopathic pharmacy is a  specialized field within the broader realm of  pharmacy that revolves around the principles and  practices of homeopathy [1]. Dr. Samuel Hahnemann  invented homeopathy in the late 18th century. It is  a holistic medical system based on the concept that  “like cures like” and emphasizes individualized  treatment tailored to the patient’s unique symptoms  [2]. In the context of homeopathic pharmacy, the  term encompasses the identification, collection,  preservation, specific preparation techniques,  combining, compounding and standardization of  medications [3]. It also covers the general operating  knowledge of the pharmaceutical industry and how  various preparations get distributed [4]. A holistic  therapeutic approach of homeopathy primarily  utilizes medicinal plants in its pharmaceutical  preparations. The collected medicinal plants undergo
Keywords: homoeopathic; Hahnemann; emphasizes